The Value Engineering Analisys Of Drainage Job (Study Case at Cluster Naraya Project of Bukit Semarang Baru) - Muhammad Afif Ridwan; Henny Pratiwi Adi; Djoko Susilo Adhy (International Conference on Coastal and Delta Areas, 2017)
Value engineering is a decision-making process based systematic and structured multi disclipinary. Drainage is a disposal water mass media in natural or artificial from the surface or subsurface of a place. In the housing scope, drainage is enabled to accomodate the flow of used water and rain water from the house which then flowed into the downstream or river as the final disposal place. The purpose of this study is to assess the initial design of the stream viewed from the cost budget plan. Find out whether the alternative design are required, find out the ideal alternative design, and get a comparison between the initial design and the alternative design. The result of this research is the analysis of budget plan, the production cost of initial design with u-ditch and buis concrete material is inefficient with budget of cost Rp. 1.781.350.200,- and then made alternative design buis concrete precast with budget of cost Rp. 1.104.667.700,- . After comparison between initial design and some alternative design, it is known that alternative design that can be recomended to be done is the alternative design with buis concrete precast material because it has lower price, by the difference of profit Rp. 676.672.500,-. Keywords : Value Engineering, Drainage